Penerapan Penyusunan Modul Digital Menggunakan Aplikasi Canva - Hartiyani, Selvi Dwi; Laksono, Eko Puji; Wicaksono, Ardy (LPPM IST AKPRIND Yogyakarta, 2023)
During the Covid-19 Pandemic in the last years, it has impac in various changes in daily life. One of them is in the education, especially the process of teaching and learning activities. Teaching and learning activities have changed from being face-to-face in the classroom to online (zoom, googlemeet etc) and needed requiring internet-based information technology devices. In order to support the learning process during the pandemic within the Proklamasi 45 University, the preparation of Digital Modules for lecturers. With the discovery learning method and training assistance, using the Canva application, lecturers are enthusiastic about making teaching materials digitally and interactively and can be used for the teaching and learning process during the Covid-19 pandemic and in the post-pandemic period.